2019
DOI: 10.1002/cctc.201901129
|View full text |Cite
|
Sign up to set email alerts
|

From Immobilization to Catalyst Use: A Complete Continuous‐Flow Approach Towards the Use of Immobilized Organocatalysts

Abstract: The combination of chiral supported‐organocatalysts and flow chemistry promotes the sustainable production of enantioenriched compounds providing a very powerful tool for chemical and pharmaceutical industries. However, the rapid deactivation of these catalysts in heterogeneous asymmetric reactions has been limiting the expansion of the area. In this work we report for the first time the advantages of synthesizing, immobilizing, and using a silica‐supported organocatalyst under a complete continuous‐flow appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…In 2019, Oliveira reported the immobilization of MacMillan catalyst supported on silica under continuous flow conditions [57] . The authors compared the activity of the catalyst immobilized on silica gel 52 under continuous flow conditions, and under batch conditions for the Diels‐Alder reaction.…”
Section: Introductionmentioning
confidence: 99%
“…In 2019, Oliveira reported the immobilization of MacMillan catalyst supported on silica under continuous flow conditions [57] . The authors compared the activity of the catalyst immobilized on silica gel 52 under continuous flow conditions, and under batch conditions for the Diels‐Alder reaction.…”
Section: Introductionmentioning
confidence: 99%
“…To solve the problem of the rapid deactivation of catalysts in heterogeneous asymmetric reactions, Finellia nd co-workers were the first to report the synthesis and immobilization of organo-catalysts under batch andc ontinuous-flow conditions. [27] The first-generation MacMillan's organocatalyst was easily synthesized from l-phenylalanine 79 and immobilized on silica through ac arbamate linkage by using batch and flow systems( Figure 25). The performance of theses ilica-supported organocatalysts 80 was investigatedi nt he Diels-Alder reaction between cyclopentadiene and E-cinnamaldehyde.…”
Section: Multi-step Continuous-flow Synthesis Using Supported Synthetmentioning
confidence: 99%
“…In 2013 Cozzi and Benaglia reported the continuous-flow stereoselective organocatalyzed Diels Alder reactions in a chiral catalytic "homemade" HPLC column [65]; the silica-supported MacMillan imidazolidinone 44 was packed into an empty stainless steel HPLC column and used to efficiently promote stereoselective Diels-Alder reactions on different substrates for more than 150 h of continuous operation [66]. Finelli et al [67] reported the in-flow preparation of the first-generation MacMillan's organocatalyst immobilized onto silica through a carbamate linkage (Figure 12). Their synthesis started from the esterification of L-phenylalanine 45 that was carried out at 50 °C in a 3 mL coil (1 hour residence time) in 90% yield, followed by the formation of the corresponding ethanolamide 46 at 60 °C, (3 mL coil, 1 hour residence time, 90% yield).…”
Section: Packed-bed Reactorsmentioning
confidence: 99%